PERAN KEBIJAKAN DIVIDEN DAN PROFITABILITAS DALAM MEMBENTUK KEBIJAKAN HUTANG PERUSAHAAN PADA SEKTOR PERBANKAN DI INDONESIA - Yolanda Yolanda; Murtianingsih Murtianingsih (POLITEKNIK LP3I JAKARTA, 2024)
This research aims to examine the influence of dividend policy and profitability on debt policy in banking companies listed on the Indonesia Stock Exchange during 2020-2022. This type of research is quantitative research, the population in this research are all banking companies listed on the Indonesia Stock Exchange during 2020-2022 and were selected using a purposive sampling technique, so that a sample of 12 companies that met the criteria was obtained. The data analysis technique used in this research is the multiple regression analysis method. This research shows that dividend policy has effect on debt policy and profitability has no effect on debt policy. Keywords : Dividend Policy, Profitability, Debt Policy